Therapy of lymphatic malformations or isolated lymphatic components in combined slow-flow malformations with bleomycin electrosclerotherapy (BEST) - Loeser, Julius Henry; Guntau, Moritz; Bidakov, Oleksandr; von der Heydt, Susanne; Gussew, Alexander; Schob, Stefan; Wohlgemuth, Walter A (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
The objective of the study was to retrospectively investigate the efficacy, technical feasibility, and patient safety of bleomycin electrosclerotherapy for lymphatic malformations and lymphatic components of combined veno-lymphatic malformations.Between May 2019 and December 2021, this retrospective, single-center study analyzed the safety and feasibility of bleomycin electrosclerotherapy in patients with lymphatic or combined veno-lymphatic malformations. The procedures, performed under imaging guidance, involved intralesional or intravenous bleomycin injection followed by reversible electroporation. Lesion sizes were measured pre- and post-treatment using T2 fatsat magnetic resonance imaging. Previous treatments, clinical symptoms, intervention details, and complications were documented and analyzed.In 21 interventions, 24 lymphatic malformations of 12 patients (mean age: 14.75 years (range: 10 days-35 years; 5 women, 7 men)) were treated. The average bleomycin dose was 3.65 mg per treatment session (range: 0.5–15 mg). Before the interventions, the mean volume of the treated malformation was 88.76 cm3 (range: 0.38–541.5 cm3) and after treatment it was 36.7 cm3 (range: 0–204.97 cm3), resulting in an average volume reduction of 54.8%. Among the observed side effects, the most frequent were a temporary postinterventional local inflammatory response and temporary skin discoloration at the injection sites. An additional improvement of clinical symptoms was achieved in all patients after a mean follow-up of 8.36 months.Bleomycin electrosclerotherapy appears to be an effective, technically feasible, and safe treatment option for patients with lymphatic malformations but further studies using a prospective approach and longer post-interventional observation period in a larger study population are required.
Keywords: vascular malformation; lymphatic malformation; retrospective study; bleomycin; bleomycin electrosclerotherapy; MR imaging